Simvastatin decreased coenzyme Q in the left ventricle and skeletal muscle but not in the brain and liver in L-NAME-induced hypertension - Kucharská, J; Gvozdjáková, A; Simko, F (Physiological research, 2007)
Inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase (statins) have been proven to reduce effectively cholesterol level and morbidity and mortality in patients with coronary heart disease and/or dyslipoproteinemia. Statins inhibit synthesis of mevalonate, a precursor of both cholesterol and coenzyme Q (CoQ). Inhibited biosynthesis of CoQ may be involved in some undesirable actions of statins. We investigated the effect of simvastatin on tissue CoQ concentrations in the rat model of NO-deficient hypertension induced by chronic L-NAME administration. Male Wistar rats were treated daily for 6 weeks with L-NAME (40 mg/kg) or with simvastatin (10 mg/kg), another group received simultaneously L-NAME and simvastatin in the same doses. Coenzyme Q(9) and Q(10) concentrations were analyzed by high performance liquid chromatography. L-NAME and simvastatin alone had no effect on CoQ concentrations. However, simultaneous application of L-NAME and simvastatin significantly decreased concentrations of both CoQ homologues in the left ventricle and slightly decreased CoQ(9) concentration in the skeletal muscle. No effect was observed on CoQ level in the liver and brain. We conclude that the administration of simvastatin under the condition of NO-deficiency reduced the level of CoQ in the heart and skeletal muscle what may participate in adverse effect of statins under certain clinical conditions.
Keywords: Coenzymes; Disease Models, Animal; NG-Nitroarginine Methyl Ester; Simvastatin; modely nemocí na zvířatech; ubichinon; oxid dusnatý; časové faktory; statiny; Male; Rats; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Brain; potkani Wistar; simvastatin; játra; Hypertension; Animals; koenzymy; Heart Ventricles; Liver; srdeční komory; zvířata; Time Factors; hypertenze; mužské pohlaví; mozek; krysa rodu Rattus; Ubiquinone; kosterní svaly; NG-nitroargininmethylester; Down-Regulation; Rats, Wistar; Muscle, Skeletal; down regulace; Nitric Oxide